The Blasphemy: Indonesia Criminal Law and Christian Perspective - Beniharmoni Harefa; Abdul Kholiq; Anugerah Tatema Harefa; Oinike Natalia Harefa; Nor Akhmal Hasmin (Universitas Negeri Semarang, 2026)
Blasphemy constitutes one of the most controversial offenses within Indonesian criminal law, particularly as governed by Article 156a of the existing Penal Code and the provisions of the 2023 Criminal Code. In a pluralistic society such as Indonesia, the enforcement of blasphemy laws frequently engenders tension between the protection of religious freedom and the maintenance of public order. This study examines the regulatory development and implementation dynamics of blasphemy laws in Indonesia, assessing the extent to which national legal norms align with international human rights principles. Employing a normative legal approach, this research analyzes statutory instruments, Constitutional Court rulings, and law enforcement practices in landmark cases such as Ahmadiyah, Ahok, and Holywings. The analysis demonstrates that existing legal norms, notably Article 156a of the Penal Code, are highly ambiguous and susceptible to abuse, disproportionately affecting minority groups. Furthermore, Constitutional Court Decision No. 140/PUU-VII/2009, which upholds the constitutionality of this article, reinforces a discriminatory status quo. Consequently, this article advocates for the statutory reformulation of these offenses utilizing a restorative justice approach, the implementation of administrative sanctions, and the strengthening of penal mediation mechanisms as stipulated in Attorney General Regulation No. 15 of 2020. The primary contribution of this research is proposing a roadmap for legal reform that strikes a balance between safeguarding religious freedom and ensuring public order, in strict compliance with international frameworks such as the ICCPR and the Siracusa Principles.